2006
DOI: 10.1007/s00125-006-0416-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the dipeptidyl peptidase-4 inhibitor sitagliptin as monotherapy in patients with type 2 diabetes mellitus

Abstract: Sitagliptin significantly improved glycaemic control and was well tolerated in patients with type 2 diabetes mellitus who had inadequate glycaemic control on exercise and diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
435
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 560 publications
(482 citation statements)
references
References 15 publications
39
435
1
7
Order By: Relevance
“…Furthermore, Raz et al. 15 reported that patients with a baseline duration of diabetes at or below the median (≤3.0 years) exhibited a greater reduction in HbA1c with sitagliptin than did patients with a baseline duration of diabetes >3.0 years. Consistent with these reports, multiple linear regression analysis in the present study revealed that baseline HbA1c levels ( P  <   0.0001) and duration of diabetes ( P  =   0.024) were independent predictors of ΔHbA1c among all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Raz et al. 15 reported that patients with a baseline duration of diabetes at or below the median (≤3.0 years) exhibited a greater reduction in HbA1c with sitagliptin than did patients with a baseline duration of diabetes >3.0 years. Consistent with these reports, multiple linear regression analysis in the present study revealed that baseline HbA1c levels ( P  <   0.0001) and duration of diabetes ( P  =   0.024) were independent predictors of ΔHbA1c among all patients.…”
Section: Discussionmentioning
confidence: 99%
“…DPP-4 inhibitors are small molecules that enhance the effects of GLP-1 and GIP, increasing glucose-mediated insulin secretion and suppressing glucagon secretion. [83,84]. The first oral DPP-4 inhibitor, sitagliptin, was approved by the Food and Drug Administration in October 2006 for use as monotherapy or in combination with metformin or TZDs.…”
Section: Medicationsmentioning
confidence: 99%
“…Another DPP-4 inhibitor, vildagliptin, was approved in Europe in February 2008, and several other compounds are under development. In clinical trials performed to date, DPP-4 inhibitors lower HbA 1c levels by 0.6-0.9 percentage points and are weight neutral and relatively well tolerated [83,84]. They do not cause hypoglycaemia when used as monotherapy.…”
Section: Medicationsmentioning
confidence: 99%
“…DPP-4 inhibition has thereby been demonstrated to be anti-diabetic both in animal models of diabetes (4)(5)(6)(7) and in patients with type 2 diabetes (8)(9)(10). The antidiabetic action of DPP-4 inhibition is explained by increased insulin secretion in association with inhibited glucagon secretion with a possible long-term action to increase β-cell mass (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%